Potensi glukomanan pada tepung porang sebagai agen anti-obesitas pada tikus dengan induksi diet tinggi lemak - Choirun Nissa; Indah Juliana Madjid (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Epidemiological studies indicate that the global prevalence of obesity has increased. Glucomannan is a water-soluble, non-starch polysaccharide, known as soluble fiber. Glucomannan has the ability to lower blood cholesterol levels and blood glucose levels, weight loss and affects the activity of intestinal and immune system function.Objective: The purpose of this study was to determine the effect of glucomannan derived from konjac flour as antiobesity agent on body weight and food intake in rats induced by high-fat diet.Method: Research was conducted in the Pharmacology Laboratory, Faculty of Medicine, University of Brawijaya. This study uses a true experimental research design. Animals were divided into six groups, normal group, normal + konjac flour, obese group, obese group + konjac flour 100 mg/kg body weight, obese group + konjac flour 200 mg/kg body weight, obese group + konjac flour 400 mg/kg.Results: Based on One-way ANOVA test, there is a significant difference (p: 0.000) on body weight after konjac flour treatment in all groups. Based on the Kruskal-Wallis test, there is a difference in food intake in various groups (p = 0.000).Conclusion: It can be concluded that glucomannan derived from konjac flour can decrease body weight and food intake in rats induced by high-fat diet.